Morel-Lavallée lesion of the elbow with ultrasound and MRI correlation - Gross, Jordan Scott (Radiol Case Rep, 2015)
Morel-Lavallée lesions are hemolymphatic, nonanatomic fluid collections that result from a separation of the subcutaneous tissue from the underlying fascia. Ultrasound and MRI characteristics of such lesions have been previously described and can be helpful in establishing a diagnosis and guiding clinical management. We present a case of a Morel-Lavallée lesion of the elbow, with ultrasound and MRI correlation, which has not been reported in the radiology literature heretofore.